SEARCHING FOR A MORAL CHARACTER: THE GENESIS OF THE AUDITOR'S DUTY - Sasongko Budisusetyo; Bambang Subroto; Rosidi Rosidi; Solimun Solimun (Journal of Economics, Business, and Accountancy Ventura, 2013)
Frequently, questions are asked to the accounting profession in the face of ethical dilemmas such as how auditors should behave. Many studies have shown moral character is important in ethical judgment, but there is very little explanation about the moral character of its own. This study aimed to test empirically the effect of individual personality factors, such as moral character variables comprising the dimensions of spirituality, idealism, moral courage, and perspective taking in the ethical judgment. Research data was obtained by distributing questionnaires to the auditor in Surabaya and Jakarta. Auditors' ethical decision-making is measured by making a story of ethical scenarios. Furthermore, the data were analyzed using software WarpPLS. This study shows importance of moral character in an auditor's ethical decision. This study shows that being an accountant is a choice being a noble human being and not a mere pursuit of economic benefits.